Environmental Legal Protection Regulation through a Judicial Process Based on Legal Certainty and Anti-SLAPP Principles - Istislam; Moch. Rif’an; Nilam Ayu Kasanah; Hezron Sabar Rotua Tinambunan; Najah Baroud (Jurnal Suara Hukum, 2026)
Indonesia, endowed with abundant natural resources, continues to face persistent environmental challenges, including pollution, land degradation, and the depletion of ecological assets. Although the legal framework, primarily Law Number 32 of 2009 on Environmental Protection and Management (UUPPLH) and its amendment under Law Number 32 of 2024, provides a normative basis for environmental governance, environmental defenders who advocate for ecological protection remain vulnerable to criminalization through Strategic Lawsuits Against Public Participation (SLAPP). This phenomenon persists despite the existence of statutory safeguards within UUPPLH, indicating the absence of a clear, coherent, and enforceable Anti-SLAPP framework in Indonesia’s positive law and reflecting insufficient governmental commitment to preventing the misuse of legal instruments to silence public participation. This study employs a normative legal research method to analyze the norms, principles, and values that underlie the protection of environmental defenders, examine the conceptual construction of Anti-SLAPP principles, and identify systemic weaknesses that allow judicial practices inconsistent with those principles to occur. The findings demonstrate an urgent need to establish adaptive and binding legal regulations through more humanistic mechanisms, along with comprehensive policy reforms within law enforcement, to ensure practical, responsive, and rights-based protection that strengthens environmental justice and democratic participation.